Electrical conductivity of soybean soaked seeds. I. Effect of genotype - Panobianco, Maristela [UNESP]; Vieira, Roberval Daiton [UNESP] (My University, 1996)
During the period from October/92 to September/94 experiments were carried out at the Seed Laboratory, FCAV/UNESP, Jaboticabal, SP, Brazil, using soybean seeds of different genotypes in order to evaluate the effect of genotype on the electrical conductivity (bulk conductivity) of soaked seeds. Seed moisture content (105 ± 3°C, 24 h), standard germination (four 50-seed samples, paper towel, 30°C), and vigor-accelerated aging (42°C, 48 h) were first determined. Undamaged soybean seeds were soaked in deionized water (four 50-seed samples, 75 ml, 25°C, 24 h) and electrical conductivity (μmhos.cm+1.g+1) was measured. Significant differences in conductivity were observed among genotypes having the same pattern of germination and vigor. The results have showed that electrical conductivity can be significantly influenced by genotype.

Durante o período de outubro/92 a setembro/94 foram conduzidos no Laboratório de Sementes do Departamento de Fitotecnia, FCAV/UNESP, Jaboticabal, SP, vários experimentos com sementes de soja, com o objetivo de avaliar o efeito do genótipo sobre a condutividade elétrica na solução de enibebição das sementes. Foram determinados: o grau de umidade das sementes(105 ± 3ºC, 24 h), a germinação-padrão (quatro repetições de 50 sementes, rolo de papel, 39ºC) e o vigor, pelo teste de envelhecimento acelerado (42ºC, 48 h) e da condutividade elétrica (quatro repetições de 50 sementes, em 75 ml de água deionizada, 25ºC, 24 h). Os resultados de condutividade elétrica mostraram diferenças significativas entre genótipos, cujas sementes apresentaram o mesmo padrão em termos de germinação e vigor (envelhecimento acelerado). Conclui-se que a condutividade elétrica na solução de embebição das sementes pode ser significativamente influenciada pelo genótipo em questão.
Condutividade elétrica na solução de embebição de sementes de soja. I. Efeito do genótipo
Keywords: Accelerated aging; Glycine max; Standard germination